ANALISIS EFISIENSI OBYEK WISATA DI KABUPATEN WONOSOBO - Agustiana, Linda; Dwi Atmanti, Hastarini (Diponegoro Journal of Economics, 2013)
Wonosobo Regency have tourism potential that has not been developed optimally. This potential can be seen from foreign tourists visiting the country with the fourth highest of all regencies in Central Java. But unfortunately from year to year conditions in Wonosobo Regency sights is getting worse and reduce the attractiveness of a tourist attraction itself. Therefore to determine the real cause, the study aims to analyze the efficiency of each of the attractions in the Wonosobo Regency. Research was conducted by interview, observation, and documentation that is of primary data and secondary data. Sampling method used is Quoted Accidental Sampling intended for anyone visitors who happened to be traveled and the added tourism managers as a key person. Number of samples is 120. The results showed that the calculation of input-output six existing attractions in Wonosobo Regency by using Data Envelopment Analysis (DEA) is known there are five attractions that have reached the level of efficiency and one of the attractions that have not been efficient, with an efficiency of only 34,25%. Attractions that have not been efficient can refer to other attractions that have been streamlined in order to improve its efficiency score.